PERANCANGAN USER INTERFACE DAN USER EXPERIENCE APLIKASI HUMAN CAPITAL BERBASIS WEB PADA PERUSAHAAN GAS XYZ MENGGUNAKAN METODE DESIGN THINKING - Dimas Aji Fuady Rokhman; Imam Ma'ruf Nugroho; Yusuf Muhyidin (INFOKOM (Informatika & Komputer), 2023)
The Human Capital Department at XYZ Karawang Gas Company manages human/employee resources as assets that the company can invest in for a long period of time to support the progress of the company and the development of the employees themselves. As in general human capital functions, the human capital of XYZ gas company also manages all employees' interests in the company. In the method development stage, after conducting interviews with 8 employees from various departments, several notes were obtained regarding the difficulties and convenience of employees in carrying out interests related to human capital. As a further development, a research method was carried out using the Design Thinking approach to create a human capital application interface. The results of the design in the form of a prototype were demonstrated to 20 employees of the XYZ gas company as respondents. After the prototype demo, 20 respondents gave scores to 28 statements based on 10 Heuristic Evaluation principles using online form questionnaire media. Based on the processing and analysis of the results of the Heuristic Evaluation, out of 28 statements as many as 24 statement items obtaining a percentage value above 65% are classified as good and very good, or the research results in the form of human capital application design have been successfully accepted by employees. While the 4 items that are classified as good enough and not good can be recommendations for design evaluation. Keywords: UI/UX, Human Capital, Design Thinking, Heuristic Evaluation